Glicoproteína-P, resistência a múltiplas drogas (MDR) e relação estrutura-atividade de moduladores P-glycoprotein and multidrug resistance: structure-activity relationships of modulators - Paula C. Huber (Química Nova, 2010)
Multidrug resistance, MDR is a major obstacle for cancer chemotherapy. MDR can be reversed by drugs that vary in their chemical structure and main biological activity. Many efforts have been done to overcome MDR based on studies of structure-activity relationships and in this review we summarize some aspects of MDR mediated by P-glycoprotein (P-gp), as the most experimentally and clinically tested form of drug resistance. The most significant MDR mechanisms revealed until now are shortly discussed. Physicochemical and structural properties of MDR modulators, measures of the MDR reversal, and QSAR studies are included.